Tourism and recreation reef advisory committee (TRRAC) 7th Meeting 13 and 14 December 2001 – Airlie Beach summary document - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 2001)
No Summary Document was issued; however, the following items were discussed during the meeting: • Framework for the management of tourism and recreation use in the Great Barrier Reef Marine Park; • Latency management in the Great Barrier Reef Marine Park; • Moorings management in the Great Barrier Reef Marine Park; • A cost benefit analysis of the management of tourism and recreation use of the Great Barrier Reef Marine Park; • Water quality in the Great Barrier Reef Marine Park; and • Report from the Tourism and Recreation Group.
Keywords: Tourism; Environmental management; Managing Multiple Use; Information Publication Scheme; Tourism; Reef-wide